Climate Change and Sub-Saharan Africa : Issues and Opportunities - Dalfelt, Arne (World Bank, Washington, DC, 2012)
Largely due to the potential threats to development, and human lives of well known climate changes, the World Bank is getting involved in a range of activities under the subject. The note focuses on climate changes in Africa, and, although it is argued that greenhouse gas (GHG) emissions from development projects in Africa should be paid minor attention, - because GHG emissions from Africa are negligible on a global scale; industrial countries should be the ones to bear major costs of reducing GHG emissions; and, due to the complex, tentative nature of potential impacts resulting from climate change - these factors do not mean that emissions are irrelevant in the African context. It is anticipated that changes in climate will result in adverse socioeconomic impacts in Africa, related to factors associated with the vulnerability of society, and the sensitivity of the environment. There is high dependency on bio-fuels, and agriculture and forestry, aggravated by restricted population mobility, poor health facilities, high population growth, and low material standards. Whereas concerns of climate change in development projects are prevalent, other factors need further attention: the trans-boundary, and global effects of climate change; cumulative effects of GHG emissions; the complexity in assessing climate change impacts at regional levels; international responsiveness to climate changes, due to the challenging nature of national sector policies, and institutional frameworks; and, the significance of climate change impacts on the socioeconomic environment.